EPIDEMIOLOGICAL STATUS OF SURGICAL AFFECTIONS OF THE BUFFALO HORN AT HOSPITAL POPULATION AND AMBULATORY VILLAGES - Mahida , H K; Tank , P H; Dhami, M A; Anne, F Karlette; Joshi, D O; Karle , A S; Vedpathak , H S (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
To know the epidemiological status of surgical affections of the horn in buffaloes, last six years’ retrospective information on surgical conditions of horn were retrieved by scrutinizing the data bank of the College Hospital as well as three villages viz., Chikhodra, Bedva and Sarsa covered under Ambulatory Clinical Services of the college. Amongst various horn pathologies recorded, the overgrown horns / misshapen horns were observed to be the highest (49.6 per cent) followed by avulsion of the horn (29.3 per cent), horn injury (9.5 per cent), septic horn / maggotted wound (6.6 per cent), fracture of horn (3.7 per cent) and broken horn (1.2 per cent). The prevalence rate of the surgical affections of horn was higher in the buffaloes ageing more than five years. The avulsion of the horn was the major affection amongst the total observed horn pathologies in Surti buffaloes. The septic horn and/or maggotted wound of the horn was more prevalent in Mehsani buffaloes.
Keywords: Buffaloes; Horn; Epidemiology